COMPARATIVE STUDY OF ANTHROPONYMS IN LANGUAGE AND CULTURE (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
Every nation has its own worldview and understanding of the world, because every person belonging to a particular society sees and understands the surrounding reality through the prism of their native language, which is a reflection of the culture of this community and serves as a means of shaping the thinking of its representatives. Due to the shift of linguistic science towards the anthropocentric paradigm of the individual as a whole and the individual in particular, interest in such a scientific direction as linguoculturology, which reflects the interconnection and interdependence of the culture and language of the people and the resulting formation of the national picture of the world, is increasing. The focus of researchers is on humanity, culture, and language. An important aspect of this relationship is the role of anthroponyms, as each nation contributes its own worldview to its own names.